DAMPAK PENGGUNAAN SMARTPHONE PADA PERILAKU KOMUNIKASI REMAJA DI JALAN BINTAN KOTA DUMAI - Ummi Aida; Tomi Hendra (ADISAM PUBLISHER, 2023)
A teenager could be addicted to playing on a smartphone, especially if the application does not contain positive educational content but contains negative educational content such as war games, board games, slots, etc. Of course, things like that are very dangerous for teenagers if left alone. This has a very bad impact on communication with the surrounding community, of course it is not easy to teach if it has become a habit for everyone. This study uses a qualitative method. Data collection was carried out by observation, interviews and documentation. The subjects of this research are teenagers on Jalan Bintan, while the research objects are the perceptions of the community and parents. The results of this research show that this research is, firstly, Intrapersonal Communication. This process helps them organize their thoughts in a more structured way and process emotions better. Second, Interpersonal Communication. The findings also reveal the negative impact of smartphone use on teenagers' intrapersonal communication. Third Communication